YY1 and CP2c in Unidirectional Spermatogenesis and Stemness - Cheon, Yong-Pil; Choi, Donchan; Lee, Sung-Ho; Kim, Chul Geun (Balsaeng'gwa saengsig, 2020)
Spermatogonial stem cells (SSCs) have stemness characteristics, including germ cell-specific imprints that allow them to form gametes. Spermatogenesis involves changes in gene expression such as a transition from expression of somatic to germ cell-specific genes, global repression of gene expression, meiotic sex chromosome inactivation, highly condensed packing of the nucleus with protamines, and morphogenesis. These step-by-step processes finally generate spermatozoa that are fertilization competent. Dynamic epigenetic modifications also confer totipotency to germ cells after fertilization. Primordial germ cells (PGCs) in embryos do not enter meiosis, remain in the proliferative stage, and are referred to as gonocytes, before entering quiescence. Gonocytes develop into SSCs at about 6 days after birth in rodents. Although chromatin structural modification by Polycomb is essential for gene silencing in mammals, and epigenetic changes are critical in spermatogenesis, a comprehensive understanding of transcriptional regulation is lacking. Recently, we evaluated the expression profiles of Yin Yang 1 (YY1) and CP2c in the gonads of E14.5 and 12-week-old mice. YY1 localizes at the nucleus and/or cytoplasm at specific stages of spermatogenesis, possibly by interaction with CP2c and YY1-interacting transcription factor. In the present article, we discuss the possible roles of YY1 and CP2c in spermatogenesis and stemness based on our results and a review of the relevant literature.